Human communication - Tubbs, Stewart L.; Moss, Sylvia (Boston : McGraw-Hill, 2000)
Human communication; Verbal and nonverbal messages; Conflict negotiation; Ethics; Intercultural communication; Interviewing; Public speaking; Mass communication.
Keywords: Communication; Human communication; Public speaking; Intercultural communication; Intercultural communication; Communication; Human communication